2020
DOI: 10.1136/bmjgh-2019-001873
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the non-specific effects of BCG vaccination on neonatal mortality: three randomised controlled trials in Guinea-Bissau

Abstract: The BCG vaccine protects non-specifically against other diseases than tuberculosis. Three randomised controlled trials of early BCG in Guinea-Bissau found a 38% reduction in all-cause neonatal mortality. Little is known about the underlying mechanisms. In Guinea-Bissau, prevalent infectious diseases display distinct seasonality. Revisiting the three trials (>6500 infants) comparing early BCG versus no early BCG in low weight infants on all-cause neonatal mortality over 12 consecutive years, we explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
(99 reference statements)
0
12
0
Order By: Relevance
“…As our main outcomes, we assessed antibody concentrations and seroprotection, but these are only surrogates of disease protection induced by vaccination. The Bacillus-Calmette-Guérin (BCG) vaccine may provide protection against other infectious diseases than tuberculosis ( 41 ) but we did not record BCG administration nor measure BCG vaccine response. In the randomized trial, we compared the MV response in infants receiving a MNP with iron to infants receiving the same MNP without iron.…”
Section: Discussionmentioning
confidence: 99%
“…As our main outcomes, we assessed antibody concentrations and seroprotection, but these are only surrogates of disease protection induced by vaccination. The Bacillus-Calmette-Guérin (BCG) vaccine may provide protection against other infectious diseases than tuberculosis ( 41 ) but we did not record BCG administration nor measure BCG vaccine response. In the randomized trial, we compared the MV response in infants receiving a MNP with iron to infants receiving the same MNP without iron.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal BCG vaccination has been shown to be associated with lower mortality rates among both TB-exposed and TB-unexposed children (Thysen et al, 2020). Three randomized controlled trials of early BCG vaccination in Guinea-Bissau found a 38% reduction in all-cause neonatal mortality (Jensen et al, 2020). These effects do not only benefit infants, as a recent clinical trial revealed that revaccinating at-risk teenagers with the BCG vaccine they first got as infants could significantly reduce the threat of these patients becoming carriers of TB infection (Nemes et al, NEJM 2018).…”
Section: Observations Of Non-specific Effects Of Bcgmentioning
confidence: 99%
“…Furthermore, trained immunity is affected by the timing of BCG administration. In clinical trials in Guinea-Bissau, BCG immunization to low-weight infants administered between November and January, during peak malaria infections, both beneficially reduced all-cause neonatal mortality and resulted in stronger responses to heterologous stimulation in whole blood assays, suggesting that there may be seasonal considerations for BCG immunization [ 51 ]. Trained immunity effects, as well as specific adaptive responses, were stronger when BCG was administered to adult volunteers in the early morning versus later in the morning, while evening vaccination produced almost no enhancement in specific and nonspecific effects [ 52 ].…”
Section: Optimizing Bcg Formulation and Delivery To Augment Innatementioning
confidence: 99%